Dental implant as an option for tooth replacement: The awareness of patients at a tertiary hospital in a developing country (2014)
Aim: A survey was set out to evaluate the knowledge of patients about tooth replacement as a whole, and assess their awareness of implant-retained prosthesis as an option of tooth replacement. Materials and Methods: Information on sociodemographic characteristics, knowledge about implant-retained tooth as an option for missing tooth replacement, cost implication, source of information and knowledge about other options of tooth replacement were obtained from patients attending the dental clinics of the University College Hospital, Ibadan, using structured self-administered questionnaires. Data were analyzed using SPSS version 20. Result: A total of 220 patients aged 18-84 years with a mean age of 37.6 (±16.5) years participated in the study, with a male to female ratio of 1:1.1. The majority (92.5%) knew that missing teeth can be replaced, while a significantly lower proportion (28.9%) knew about dental implants as an option (P < 0.01). Dentists were the major source of information on dental implants (68%). Only 21 (36.8%) of those who had heard about dental implant had knowledge about the cost (P < 0.000). Conclusion: A low level of awareness about dental implant as tooth replacement option exist in this environment, although most of the study participants were aware that missing teeth can be replaced